Small Historic Towns in Lithuania and Issues of their Contemporary Architectural Identity: The Case of Merkinė - Buržinskas, Žygimantas (Lietuvos istorijos studijos, 2025)
The article investigates the issues of architectural development of Merkinė, a small historic town, in the 20th and 21st centuries, which is notable for the devastation suffered during World War Two, changes caused by Sovietization, and the attempts of the recent decades to define the concept(s) of the development of a historic site. The article notes the activity of Dzūkija National Park, the Department of Cultural Heritage under the Ministry of Culture, and Varėna District Municipality on the architectural development of the small town of Merkinė. The research has revealed that, so far, there is no clear legal basis defining the development of the historic center of Merkinė, and that some legal regulations defining construction are not in line with the urbanist logic of a minor town, as developed prior to World War Two. The article submits proposals and lists potential actions regarding alterations in the development of this small town so that the historic urbanist identity of Merkinė could be defined more emphatically.
Keywords: architecture of small towns; old town; protected areas; Merkinė; Lithuania in 1918–1940